STRATEGI DIGITAL MARKETING MENGGUNAKAN MEDIA SOSIAL DAN E-COMMERCE DALAM PENGEMBANGAN BISNIS UMKM YASMIN'S BROWNIES - Nadiya Nur Arafah; Shevia; Mutiara Kamila; Chyntia Huang; Renza Fahlevi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Small and medium enterprises (SMEs) play a crucial role in maintaining the stability and balance of the national economy, therefore each SME is entitled to special rights and powers in conducting their business. One of those powers requires that every SME is able to adapt and follow the tren of economic movement that tends to utilize digital technology. This research aims to determine the impact of Digital Marketing Strategies Using Social Media and E-Commerce on the Development of Yasmin's Brownies SME Business. This research uses a descriptive-qualitative research design utilizing primary and secondary data sources obtained through observations conducted through interviews and surveys conducted by distributing questionnaires. This research resulted in the impact of digital marketing on Yasmin's Brownies SME by utilizing the digital media platform Instagram as a marketing media and expanding the marketing and sales reach of the SME using the e-commerce platform Tokopedia. The impact of this research aims to provide solutions to marketing problems faced by SMEs that are starting to venture into digital media in the process of marketing their products to consumers in a wider reach.